Provivienda: A Factor in the Squatter (2014)
This article reconstructs the history of Provivienda, with regards to the concept of squatter colonization, and interprets Provivienda’s organizational structure through interviews with surviving founders of these squatter shantytowns as well as through documents from the archives of the organization. Created in 1959 and still operating, Provivienda was the irst social organization of homeless individuals, consistingof victims of forced displacement that sought shelter and obtained their own housing through collective action. Many of its founders, who started coffee farms by squatting on public land, had been dispossessed by the violence of the 1950’s. Theylater squatted on public lands and vacant municipal properties in population centers and formed part of the Patriotic Union political party. Currently, Provivienda organizes homeless individuals into a movement of tenants and advocates for their full inclusion as citizens with the right to a decent home. A relection on this historical process from the view of current political negotiation between insurgent groups and the government may contribute to the understanding of the causes of the national conlict and to the building of peace with social justice.